MANAJEMEN OPERASI PRODUSEN BENIH TERHADAP PENANGKAR BENIH PADI DI DUA KECAMATAN KABUPATEN BANTUL, DIY - Sulastiyah, Amie (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
Increased rice production in the Special Effort program, its development using the System of Rice Intensification. Provision of seed is urgent. Germination gradually handed over to private parties through multiple seed producers and its breeder located in the village / District. The government only plays a role in setting the policy, guidance, research and monitoring. The problem is in every manufacturer in cooperation / partnership are problem is in each producer that management is not equal to one another because it depends on the culture of producers and growers. From the condition, carried out research in May to October 2015, with the aim of knowing how the implementation of the operational management of rice seed in the district of Bantul. The study was conducted by survey and interview 29 breeders and 7 producers. The result: all manufacturers in the survey locations, all manufacturers treated equally in provision of inputs, processes, operation and sustainability of the partnership. The difference is four manufacturers in the form of cash and 3 in the form of means of production. Transformation for, three manufacturers used trained personnel, 2 Manufacturers used specialized personnel and 2 Manufacturers used inexperienced personnel. The sustainability of the partnership by five manufacturers and the two producers did not continue. Continuity producers with breeder emphasis on openness and trust. Breeder generally managed by individual manufacturers and government agencies run more sustainable in every season, compared to manufacturers who have a centralized organization.